CEO leadership behaviors, organizational performance, and employees' attitudes - Wang, Hui; Tsui, Anne S.; Xin, Katherine R. (The Leadership quarterly)
This study explores the links between CEO leadership behaviors, firm performance and employees' attitudes in a sample drawn from 125 firms in China. We first inductively identified categories of CEO leadership behaviors in the Chinese context. Through a factor analysis, we developed a six-dimension measure of CEO leadership behaviors, with three dimensions focused on tasks and three dimensions focused on relationships. Our hypotheses were tested on a matched data set including 739 middle managers and their supervisors (top managers) in the 125 firms. Results from the structural equation modeling analysis show that the CEO's task-focused behaviors are directly linked to firm performance. The CEO's relationship-focused behaviors are related to employees' attitudes and, through these attitudes, to firm performance. Limitations and implications for future research are discussed.